2011
DOI: 10.1038/cr.2011.149
|View full text |Cite
|
Sign up to set email alerts
|

A network-based gene-weighting approach for pathway analysis

Abstract: Classical algorithms aiming at identifying biological pathways significantly related to studying conditions frequently reduced pathways to gene sets, with an obvious ignorance of the constitutive non-equivalence of various genes within a defined pathway. We here designed a network-based method to determine such non-equivalence in terms of gene weights. The gene weights determined are biologically consistent and robust to network perturbations. By integrating the gene weights into the classical gene set analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 57 publications
0
52
0
Order By: Relevance
“…a gene regulatory network, or a co-expression network, can be generally estimated by correlation coefficients of molecule pairs from expression or sequence data of multiple samples. Based on biological and clinical data, a number of network-based methods were proposed not only to identify disease modules and pathways but also to elucidate molecular mechanisms of disease development at the network level (57). To determine a person's state of health, many studies have shown that network-based biomarkers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…a gene regulatory network, or a co-expression network, can be generally estimated by correlation coefficients of molecule pairs from expression or sequence data of multiple samples. Based on biological and clinical data, a number of network-based methods were proposed not only to identify disease modules and pathways but also to elucidate molecular mechanisms of disease development at the network level (57). To determine a person's state of health, many studies have shown that network-based biomarkers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because miRNA regulates target genes at both the mRNA and the protein levels (12,27,29,30), traditional methods simply using gene expression value for genemiRNA pair prediction may fail to pick up those genes with mainly protein level changes. To overcome this problem, we have taken advantage of the gNET previously established based on protein-protein interactions, co-annotations, and gene coexpressions and assigned a gene with an activity measure dependent on the expression level of its functional associated genes (16). We then integrated this method with TargetScan to identify gene-miRNA pairs significantly deregulated in cancer glycolysis (Fig.…”
Section: Establishment Of Algorithm For Prediction Of Deregulated Glymentioning
confidence: 99%
“…We have previously constructed a comprehensive gene functional association network, gNET, by integration of datasets including protein-protein interactions, gene co-annotations, and gene co-expressions, which were successfully applied to the development of a novel Gene Association Network-based Pathway Analysis (GANPA) (16). Here we have taken advantage of the gNET and applied it to the prediction of deregulated genemiRNA pairs via calculation of gene activity.…”
mentioning
confidence: 99%
“…Additionally, our method inferred the distributions of gene memberships in each pathway by looking at per-pathway gene distributions. The significance of those genes with high probabilities in the gene distributions should be further investigated as signatures of each pathway (Fang et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This premise did not reflect the realistic processes occurred in a cell. For instance, genes at upstream could affect more genes within a pathway than those at downstream (Fang et al, 2011). In addition, despite being closely related, the LDA model relaxes linear constraints used in the matrix factor model.…”
Section: Introductionmentioning
confidence: 98%